PEMANFAATAN MEDIA TIKTOK SEBAGAI SARANA PENGENALAN AYAT-AYAT AL-QUR’AN PADA ANAK USIA DINI - Aisyah Mahfudziyah; Asih Ulfiah; Aisah; Neneng Masrurh; Alam Tarlam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the utilization of TikTok as a medium for introducing Qur’anic verses to early childhood learners and analyzes its potential and challenges within the context of Islamic education. The research is motivated by the increasing exposure of young children to digital media, which presents both educational opportunities and pedagogical risks. This study employs a library research method with a descriptive-analytical approach. Data were collected from scholarly books, journal articles, and relevant academic publications on Qur’anic learning, digital media, and early childhood development. The findings indicate that TikTok has the potential to function as a supportive medium for introducing Qur’anic verses through its audio-visual features, short video duration, and repetition mechanisms that align with early childhood learning characteristics. However, its use requires strict content selection, parental and teacher supervision, and reinforcement of proper etiquette in Qur’anic learning to avoid distraction, superficial understanding, and the loss of the sacred value of the Qur’an. With appropriate management, TikTok can serve as an effective complementary medium for Qur’anic education in early childhood.